The Potential of Integrated Video and Vehicle Forensic Investigation - S. S. Zharkikh; A. A. Godlevskii; S. A. Krivoshchekov (Теория и практика судебной экспертизы)
In some cases, the material provided for a forensic vehicle examination may be insufficient to answer the questions placed before the experts. However, sometimes there are some multimedia files presented which by means of forensic video examination can help to discover the information missing for implementation of the vehicle expertise. This article reviews the potential of forensic video and vehicle investigations when conducting an integrated research including the investigation of circumstances of a road traffic accident. The examples from the state experts’ practice of the forensic institutions of the Russian Ministry of Justice are provided. This review is intended to introduce the video experts and the vehicle experts to the opportunities there are in the integrated research of the mechanism of road accidents.